PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOMETHINC - Diva Yasmin; Triaji Pratomo (FEB Universitas Sam Ratulangi Manado, 2023)
Currently, Indonesia has many cosmetic and skin care brands that are popular with teenagers and adult women,one of which is the Somethinc brand. Somethinc product is one of the local serum champions in Indonesia whocan grasp the beauty and skin care needs of women and men with diverse skin conditions for consumers. Increasing in the cosmetics and skin care sector is due to encouragement from influential people such asinfluencers on social media who often make evaluations about cosmetic or skin care goods and display how theyutilize their products to their followers. This research was undertaken to assess the effect of pricing and promotionon purchasing decisions for Somethinc goods.The sort of research used is descriptive research employingquantitative research methods. The sampling approach is non-probability sampling technique with 100respondents. The data analysis technique uses descriptive analysis and multiple linear regression.The results ofthis descriptive study reveal that prices, promotions, and purchase decisions are included in the positive category. The results of multiple linear regressions suggest that the effect of price and promotion on purchase decisions hasa coefficient of determination of 85.4% influencing purchasing decisions, the remaining 14.6% is influenced byother independent factors not explored in this study.